Comparison Of Direct Regional Head Election Systems In The Context Of Global Construction Law - Mannan, Khaerul (IJBLE Scientific Publications Community Inc., 2023)
This article analyzes the comparison of regional head election systems directly in the context of global constitutional law. The background to this research is driven by the complexity and diversity of regional head election systems implemented in various countries, as well as their impact on global state governance which is increasingly connected and interdependent. The main objective of this research is to understand the differences and similarities in these systems, identify the factors that influence the choice of the regional head election system, and explore the implications for global constitutional law issues. The research methods used involve literature analysis, comparative studies, and a review of various regional head election models, both based on direct elections and representative systems. The research results show that the direct regional head election system has the potential to increase public participation and accountability, by focusing on democratic principles. However, its implementation can also pose challenges, such as fragile political stability and the protection of minority rights which is often a concern. This research concludes that a deeper understanding of the direct regional head election system and its implications for global state governance is very important in efforts to build global statecraft law that is more inclusive and sustainable. This article contributes to the literature discussing global constitutional law issues and can be a guide for researchers, legal practitioners, and policymakers in planning and evaluating regional head election systems.